2009
DOI: 10.1021/ja907054y
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Histidine-Catalyzed Cross-Aldol Reactions of Enolizable Aldehydes: Access to Defined Configured Quaternary Stereogenic Centers

Abstract: A histidine-catalyzed asymmetric direct cross-aldol reaction of enolizable aldehydes is described. In contrast to proline, histidine is able to clearly differentiate the reactivity of various aldehydes. In addition, this approach provides access to syn-configured beta-hydroxyaldehydes. Thus, by application of this new methodology, defined-configuration quaternary stereocenters can be constructed with ease. The utility of this method is demonstrated in several total syntheses of branched-chain carbohydrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 38 publications
0
50
0
1
Order By: Relevance
“…A diamine containing two pyrrolidine moieties, in conjunction with an acid cocatalyst, was identified by Barbas 32 to promote highly enantioselective aldol reactions of isobutyraldehyde and other α,α-dialkyl aldehydes as donors, although only non-enolizable, aromatic aldehydes were used as acceptors. We found, 31 however, that in the presence of histidine as catalyst, α-branched aldehydes react as donor components with a variety of enolizable aldehydes such as 1a – g , including electron-deficient aldehydes, forging quaternary stereogenic centers with defined configurations in the aldol products with remarkable ease (Scheme 1). The enantioselectivities in the isolated β-hydroxyaldehydes 2a – g were good to excellent.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A diamine containing two pyrrolidine moieties, in conjunction with an acid cocatalyst, was identified by Barbas 32 to promote highly enantioselective aldol reactions of isobutyraldehyde and other α,α-dialkyl aldehydes as donors, although only non-enolizable, aromatic aldehydes were used as acceptors. We found, 31 however, that in the presence of histidine as catalyst, α-branched aldehydes react as donor components with a variety of enolizable aldehydes such as 1a – g , including electron-deficient aldehydes, forging quaternary stereogenic centers with defined configurations in the aldol products with remarkable ease (Scheme 1). The enantioselectivities in the isolated β-hydroxyaldehydes 2a – g were good to excellent.…”
Section: Introductionmentioning
confidence: 98%
“…We recently reported 31 that the readily available histidine is a superior catalyst to facilitate the onepot, cross-aldol reaction of two dissimilar enolizable aldehydes, without the need for any specialized experimental setup. As reviewed recently by List, 8 α-branched aldehydes such as isobutyraldehyde, are typically used as electrophiles in asymmetric enamine catalysis including organocatalyzed aldol reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the secondary amines and related peptides catalyzed aldol reaction, primary amino acid and primary amines have also shown to act as efficient organocatalysts in enantioselective aldol reactions (267,268). In the organocatalytic aldol reaction, an important and synthetically useful achievement is the direct catalytic asymmetric cross-aldol addition between various enolizable aldehydes (269). Subsequently, a number of research groups have reported enantio-and diastereoselective variants of proline and proline-derived functional secondary amines catalyzed aldol reaction.…”
Section: Metal-free Catalystsmentioning
confidence: 99%
“…10 Over the past decade, a number of similar syn-aldol reactions have been realized in laboratory (though, with a somewhat lower stereoselectivity) in the presence of properly designed primary aminocatalysts. Among them, O-protected serine or threonine amino acids, [11][12][13][14][15][16] their amides, 17 valine, 18 leucine, 19 iso-leucine 20 or tert-leucine derivatives 21 and some primary-tertiary 1,2-diamine organocatalysts [22][23][24][25][26][27] exhibited promising catalytic performance. However, unlike enzymes, these valuable catalysts could be used just once and until recently no information on their recovery and reuse in the catalytic process has been available.…”
Section: Introductionmentioning
confidence: 99%